THE ROLE OF SOCIAL WORK AGENCIES IN PROMOTING ELDERLY WELFARE IN KAYUNGA VILLAGE; A CASE OF ROTOM - KEBIRUNGI TRACY (Uganda Christian University, 2025)
The study titled “The Role of Social Work Agencies in Promoting Elderly Welfare in Kayunga Village: A Case of ROTOM” was conducted to examine how social work agencies support older persons, guided by three objectives: identifying the social work services provided by ROTOM, assessing the social needs of the elderly, and exploring the challenges faced in service delivery. Using a sample size of 63 respondents, findings showed that ROTOM provides home care, health referrals, counselling, financial assistance, and social support groups, with financial assistance (62%) and social support groups (61%) being most effective, and regression analysis confirming a significant positive effect on elderly welfare (Beta = 0.153, p = 0.007, Adjusted R² = 0.096). Social needs such as healthcare access (80%) and companionship (56%) were critical, though financial stability remained weak, and regression results showed significant influence on welfare (Beta = 0.224, p = 0.015, Adjusted R² = 0.077). Challenges included stigma and ageism (75%), shortage of trained social workers (62%), and limited awareness (68%), though regression analysis showed their effect was weak (Beta = 0.091, p = 0.169, Adjusted R² = 0.021). The study concludes that social work services, though impactful, remain under-resourced; addressing social needs is vital for welfare improvement; and systemic barriers undermine service delivery. It recommends that the government should strengthen funding, integrate elderly care into national programs, enhance social worker capacity, and expand awareness and anti-stigma initiatives to ensure inclusive and sustainable elderly welfare in Uganda.
UNDERGRADUATE RESEARCH